Antibacterial rare earth stab-proof rubber product and preparation method thereof
By using nano-grade rare earth composite materials in rubber products, the shortcomings of existing anti-needle rubber products in terms of material strength and flexibility balance and durability are solved, and higher anti-puncture and antibacterial properties are achieved, effectively protecting medical staff from needle-punch injuries.
Patent Information
- Application Number
- CN202411614455.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing anti-needle rubber products have shortcomings in the balance of material strength and flexibility and durability, making it difficult to effectively protect medical staff from the dangers of needle stab injuries.
Using nano-scale rare earth composite materials, a rare earth composite material with a layered structure is prepared by reacting modified rare earth nitric acid with gluconic acid and ammonium bicarbonate, and it is evenly dispersed in rubber products to improve its anti-puncture and antibacterial properties.
It significantly improves the anti-puncture performance and antibacterial ability of rubber products, can more effectively protect medical staff from the harm of needle stab injuries, and at the same time improves the durability of the product.
Smart Images

Figure CN119144060B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of rubber products, and in particular relates to an antibacterial rare earth puncture-proof rubber product and a preparation method thereof. Background Art
[0002] In the medical field, the harm of needlestick injuries to medical staff cannot be ignored. After a needlestick injury, the biggest risk faced by medical staff is infection with various pathogens, especially blood-borne diseases, such as hepatitis B (HBV), hepatitis C (HCV), and AIDS (HIV). Once infected, these pathogens may lead to chronic diseases, various complications, and even death. In addition, medical staff often have strong psychological problems such as fear and anxiety after a needlestick injury. These psychological problems not only affect their daily work and life, but may also lead to the occurrence of psychological diseases such as insomnia and depression. Therefore, the harm of needlestick injuries to medical staff in the medical field is multifaceted, including infection with pathogens, psychological impact, occupational safety threats, etc. In order to reduce the occurrence of needlestick injuries, medical staff need to improve their awareness of protection. At the same time, the selection of stab-proof gloves should attract more attention from medical staff.
[0003] Studies have shown that after rare earth materials are doped into the rubber of gloves, rare earth elements are introduced into polymer materials through melt blending and other methods, and rare earth layered structural materials with high temperature resistance and chemical stability can be prepared. This material can make ordinary rubber gloves have stronger puncture resistance. In addition, nanotechnology has been widely studied in the field of materials. Compared with the original materials, the microstructure of nanomaterials after reducing the particle size has been significantly improved. After being applied to rubber, the strength and toughness of gloves can be significantly improved, thereby improving the puncture resistance. With the continuous development of the medical industry and the improvement of people's health awareness, the market size of puncture-proof gloves is also expanding. The global protective gloves market value has reached approximately US$3.5 billion in 2023 and is expected to grow at an annual compound growth rate of more than 6%. Among them, the medical field has always been one of the main application areas of protective gloves. While the market size is expanding, the market share of puncture-proof gloves is also increasing. With the continuous development of the medical industry and the improvement of people's health awareness, the market demand for puncture-proof gloves will continue to grow in the future. In addition to traditional surgical and operation fields, the application areas of puncture-proof gloves are also expanding. For example, in the fields of nursing, first aid, laboratories, etc., medical staff also need to use puncture-proof gloves to protect their hands. In addition, with the improvement of people's awareness of personal protection, puncture-proof gloves are gradually being used in other fields such as home and industry.
[0004] In summary, the application prospects of puncture-proof gloves in the medical field are very broad. At present, the technical bottlenecks of needle-proof rubber products on the market are mainly the balance between material strength and flexibility, as well as durability. The special properties of rare earth materials will overcome the above problems to a certain extent, giving the product more practical performance. With the continuous development of the medical industry and the improvement of people's health awareness, the market demand for puncture-proof gloves will continue to grow. At the same time, with the continuous advancement of technology and the continuous upgrading of products, the performance of puncture-proof gloves will be further improved, providing more comprehensive and effective protection for medical staff. Summary of the invention
[0005] In view of this, the present invention aims to overcome the defects in the prior art and proposes an antibacterial rare earth stab-proof rubber product and a preparation method thereof.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] The present invention provides an antibacterial rare earth stab-proof rubber product, which comprises the following raw materials in parts by weight:
[0008] 80-120 parts of rubber latex, 3-7 parts of curing agent, 3-7 parts of dispersant, 1-2 parts of rare earth composite material;
[0009] The preparation method of the rare earth composite material comprises the following steps:
[0010] Step 1 is to add modified rare earth nitrate and gluconic acid into deionized water, and obtain a modified rare earth nitrate-gluconic acid aqueous solution after complete dissolution;
[0011] Step 2 is to add ammonium bicarbonate into deionized water and obtain an ammonium bicarbonate aqueous solution after the ammonium bicarbonate is completely dissolved;
[0012] Step 3 is to slowly drop the aqueous ammonium bicarbonate solution into the modified rare earth nitrate-gluconic acid aqueous solution, and then filter, wash, dry, calcine, grind, sand mill, and vacuum dry to obtain the rare earth composite material.
[0013] Furthermore, the solid-liquid ratio of the modified rare earth nitrate, gluconic acid and deionized water in step 1 is 2-11 g: 1-2 g: 35-45 mL; the solid-liquid ratio of ammonium bicarbonate and deionized water in step 2 is 2-5 g: 15-25 mL.
[0014] Furthermore, the volume ratio of the aqueous solution of ammonium bicarbonate to the aqueous solution of modified rare earth nitrate-gluconic acid in step 3 is 8-10:18-22.
[0015] Furthermore, the drying step in step 3 is performed at a temperature of 70-90°C for 10-15 hours; the calcining step in step 3 is performed at a temperature of 700-750°C for 2-4 hours; and the sanding step in step 3 is wet sanding at a rate of 2500-3000 r / min for 2-4 hours.
[0016] Furthermore, the preparation method of the modified rare earth nitrate in step 1 comprises the following steps:
[0017] The mushroom dregs powder is added to a sodium hydroxide solution, and after stirring evenly, a rare earth nitrate solution is added thereto, and after mixing evenly, the obtained mixed solution is subjected to magnetic stirring under heating conditions. After the reaction is completed, the modified rare earth nitrate is obtained after drying, grinding, and sieving.
[0018] Furthermore, the mass concentration of the sodium hydroxide solution is 3-5%; the concentration of the rare earth nitrate solution is 0.2-1.0 mol / L.
[0019] Furthermore, the solid-to-liquid ratio of the mushroom bran powder to the sodium hydroxide solution and the rare earth nitrate solution is 1-2g: 15-25mL: 15-25mL.
[0020] Furthermore, the temperature of the heating step in the preparation method of the modified rare earth nitrate is 70-80°C; the speed of the magnetic stirring step in the preparation method of the modified rare earth nitrate is 600r / min, and the time is 0.5-1.0 hour; the temperature of the drying step in the preparation method of the modified rare earth nitrate is 70-90°C, and the time is 16-32 hours; the mesh number of the sieve in the screening step in the preparation method of the modified rare earth nitrate is 200-300 mesh.
[0021] Furthermore, the rare earth nitrate in the rare earth nitrate solution is at least one of cerium nitrate hexahydrate, lanthanum nitrate hexahydrate or yttrium nitrate hexahydrate.
[0022] The present invention also provides a method for preparing an antibacterial rare earth stab-proof rubber product, comprising the following steps: mixing rubber latex, a curing agent, a dispersant and a rare earth composite material, demoulding, drying, vulcanizing and washing to obtain the antibacterial rare earth stab-proof rubber product.
[0023] Furthermore, the temperature of the mixing step is 110° C.-150° C.; the temperature of the drying step is 70° C.-90° C. for 10-15 hours.
[0024] Cellulose, lignin and other substances in mushroom bran powder can effectively adsorb rare earth ions in rare earth nitrates, providing them with a large number of adsorption sites, making them more stably adsorbed on their surfaces or in gaps; at the same time, due to the functional groups in mushroom bran powder (such as carboxyl, hydroxyl, carbonyl, O-glycosidic bond, etc.) when mixed with rare earth nitrates, they can chelate with the rare earth ions therein to form a chelate complex with a ring structure, thereby enhancing the stability of rare earth nitrates, so that the rare earth ions can more effectively exert their own effects.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] The antibacterial rare earth puncture-proof rubber product of the present invention is prepared by using a nano-scale rare earth composite material. The rare earth composite material is evenly and stably dispersed in the rubber product, and the nano-scale rare earth composite material can further enhance the antibacterial performance of the rubber product by utilizing its small size effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A bar graph showing the puncture resistance of the rubber product according to the embodiment of the present invention;
[0028] Figure 2 This is a colony diagram of the rubber product against Escherichia coli described in an embodiment of the present invention;
[0029] Figure 3 This is a colony diagram of the rubber product described in the embodiment of the present invention against Staphylococcus aureus. DETAILED DESCRIPTION
[0030] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0031] The present invention will be described in detail below with reference to the embodiments.
[0032] Example 1
[0033] A method for preparing an antibacterial rare earth stab-proof rubber product comprises the following steps:
[0034] (1) Weigh 40 g of sodium hydroxide, dissolve it with deionized water and make it up to 1.0 L, then add 100 g of fungus dregs powder, stir and dissolve it for later use; weigh 216.51 g of lanthanum nitrate hexahydrate, and make it up to at least 1.0 L with deionized water for later use; then mix the rare earth nitrate solution and fungus dregs powder solution in a volume ratio of 2:1, place the mixed solution system in a magnetic stirrer, set the rotor speed to 600 r / min, the temperature to 75 °C, and the stirring time to 0.5 h. After the reaction is completed, transfer it to an evaporating dish and place it in an oven at 80 °C for 24 h. After drying, transfer the solid to a mortar and grind it, pass it through a 200-mesh sieve, and the obtained powder is the modified rare earth nitrate;
[0035] (2) Weigh 800 g of modified rare earth nitrate and 80 g of gluconic acid into a beaker, add 3.2 L of deionized water, and stir with a glass rod until completely dissolved for later use; weigh 260 g of ammonium bicarbonate into a beaker, add 1.6 L of deionized water, and stir with a glass rod until completely dissolved for later use; then add the aqueous solution of ammonium bicarbonate into a separatory funnel and slowly drip it into the prepared aqueous solution of modified rare earth nitrate-gluconic acid. During the dripping process, a large amount of white precipitate will be observed in the mixed solution; let the mixed solution stand in the beaker for 30 min, discard the clear supernatant, and then transfer the white precipitate at the bottom into a Buchner funnel lined with filter paper and filter it with a suction filter. After filtering, take the white solid into an evaporating dish and place it in an oven at 80°C for 12 h for drying. After drying, transfer the white solid into a crucible and place it in a muffle furnace for calcination at 750°C for 3 h, the calcined solid is ground into fine powder using a grinder, and then prepared into an aqueous solution with a solid content of 25% using deionized water, and placed in a sand mill for wet sand grinding at 3000 r / min for 2 h. The sand-milled slurry is placed in a vacuum drying oven for full drying, and the dried solid is finally ground into fine powder using a grinder again to obtain a rare earth composite material with a layered structure;
[0036] (3) Take 10 L of natural rubber latex, add 500 mL of curing agent 8530, 500 mL of dispersant 2120, and 100 g of rare earth composite material, mix the above materials and add them to a mixer, heat the mixer to 120°C, and use high-speed stirring to form a rubber liquid with a uniform mixture of raw materials; fully immerse the mold in the rubber liquid and rotate it horizontally for 10 min to ensure that the rubber liquid covers the glove mold, and then transfer the mold to an oven for drying at 80°C for 12 h; after drying, transfer the mold to a vulcanization chamber for vulcanization treatment, and then use infrared treatment to completely evaporate the moisture inside the product, and then use deionized water to clean the dust and impurities on the surface, and then transfer it to an oven for drying again. After the above series of treatments, the product has better toughness and strength and can be directly demolded manually.
[0037] Comparative Example 1
[0038] A method for preparing an antibacterial rare earth stab-proof rubber product comprises the following steps:
[0039] (1) Weigh 40 g of sodium hydroxide, dissolve it with deionized water and make it up to 1.0 L, then add 100 g of mushroom husk powder, stir and dissolve it for later use, weigh 216.51 g of lanthanum nitrate hexahydrate, and make it up to at least 1.0 L with deionized water for later use; then mix the rare earth nitrate solution and the mushroom husk powder solution in a volume ratio of 2:1, transfer the mixed solution system into an evaporating dish, place it in an oven and set the conditions: 80°C, 24 h, transfer the dried solid into a mortar and grind it, and pass it through a 200-mesh sieve to obtain a powder that is the modified rare earth nitrate;
[0040] (2) Weigh 800 g of modified rare earth nitrate and 80 g of gluconic acid into a beaker, add 3.2 L of deionized water, and stir with a glass rod until completely dissolved for later use; weigh 260 g of ammonium bicarbonate into a beaker, add 1.6 L of deionized water, and stir with a glass rod until completely dissolved for later use; then add the aqueous solution of ammonium bicarbonate into a separatory funnel and slowly drip it into the prepared aqueous solution of modified rare earth nitrate-gluconic acid. During the dripping process, a large amount of white precipitate will be observed in the mixed solution; let the mixed solution stand in the beaker for 30 min, discard the clear supernatant, and then transfer the white precipitate at the bottom into a Buchner funnel lined with filter paper and filter it with a suction filter. After filtering, take the white solid into an evaporating dish and place it in an oven at 80°C for 12 h for drying. After drying, transfer the white solid into a crucible and place it in a muffle furnace for calcination at 750°C for 3 h, the calcined solid is ground into fine powder using a grinder, and then prepared into an aqueous solution with a solid content of 25% using deionized water, and placed in a sand mill for wet sand grinding at 3000 r / min for 2 h. The sand-milled slurry is placed in a vacuum drying oven for full drying, and the dried solid is finally ground into fine powder using a grinder again to obtain a rare earth composite material with a layered structure;
[0041] (3) Take 10 L of natural rubber latex, add 500 mL of curing agent 8530, 500 mL of dispersant 2120, and 100 g of rare earth composite material, mix the above materials and add them to a mixer, heat the mixer to 120°C, and use high-speed stirring to form a rubber liquid with a uniform mixture of raw materials; fully immerse the mold in the rubber liquid and rotate it horizontally for 10 min to ensure that the rubber liquid covers the glove mold, and then transfer the mold to an oven for drying at 80°C for 12 h; after drying, transfer the mold to a vulcanization chamber for vulcanization treatment, and then use infrared treatment to completely evaporate the moisture inside the product, and then use deionized water to clean the dust and impurities on the surface, and then transfer it to an oven for drying again. After the above series of treatments, the product has better toughness and strength and can be directly demolded manually.
[0042] Comparative Example 2
[0043] A method for preparing an antibacterial rare earth stab-proof rubber product comprises the following steps:
[0044] (1) Weigh 40 g of sodium hydroxide, dissolve it with deionized water and make it up to 1.0 L, then add 20 g of fungus dregs powder, stir and dissolve it for later use; weigh 216.51 g of lanthanum nitrate hexahydrate, and make it up to at least 1.0 L with deionized water for later use; then mix the rare earth nitrate solution and fungus dregs powder solution in a volume ratio of 2:1, place the mixed solution system in a magnetic stirrer, set the rotor speed to 600 r, the temperature to 75 °C, and the stirring time to 0.5 h. After the reaction is completed, transfer it to an evaporating dish and place it in an oven at 80 °C for 24 h. After drying, transfer the solid to a mortar and grind it, pass it through a 200-mesh sieve, and the resulting powder is the modified rare earth nitrate;
[0045] (2) Weigh 800 g of modified rare earth nitrate and 80 g of gluconic acid into a beaker, add 3.2 L of deionized water, and stir with a glass rod until completely dissolved for later use; weigh 260 g of ammonium bicarbonate into a beaker, add 1.6 L of deionized water, and stir with a glass rod until completely dissolved for later use; then add the aqueous solution of ammonium bicarbonate into a separatory funnel and slowly drip it into the prepared aqueous solution of modified rare earth nitrate-gluconic acid. During the dripping process, a large amount of white precipitate will be observed in the mixed solution; let the mixed solution stand in the beaker for 30 min, discard the clear supernatant, and then transfer the white precipitate at the bottom into a Buchner funnel lined with filter paper and filter it with a suction filter. After filtering, take the white solid into an evaporating dish and place it in an oven at 80°C for 12 h for drying. After drying, transfer the white solid into a crucible and place it in a muffle furnace for calcination at 750°C for 3 h, the calcined solid is ground into fine powder using a grinder, and then prepared into an aqueous solution with a solid content of 25% using deionized water, and placed in a sand mill for wet sand grinding at 3000 r / min for 2 h. The sand-milled slurry is placed in a vacuum drying oven for full drying, and the dried solid is finally ground into fine powder using a grinder again to obtain a rare earth composite material with a layered structure;
[0046] (3) Take 10 L of natural rubber latex, add 500 mL of curing agent 8530, 500 mL of dispersant 2120, and 100 g of rare earth composite material, mix the above materials and add them to a mixer, heat the mixer to 120°C, and use high-speed stirring to form a rubber liquid with a uniform mixture of raw materials; fully immerse the mold in the rubber liquid and rotate it horizontally for 10 min to ensure that the rubber liquid covers the glove mold, and then transfer the mold to an oven for drying at 80°C for 12 h; after drying, transfer the mold to a vulcanization chamber for vulcanization treatment, and then use infrared treatment to completely evaporate the moisture inside the product, and then use deionized water to clean the dust and impurities on the surface, and then transfer it to an oven for drying again. After the above series of treatments, the product has better toughness and strength and can be directly demolded manually.
[0047] Comparative Example 3
[0048] A method for preparing an antibacterial rare earth stab-proof rubber product comprises the following steps:
[0049] (1) Weigh 216.51 g of lanthanum nitrate hexahydrate and 80 g of gluconic acid into a beaker, add 3.2 L of deionized water, and stir with a glass rod until completely dissolved for later use; weigh 260 g of ammonium bicarbonate into a beaker, add 1.6 L of deionized water, and stir with a glass rod until completely dissolved for later use; then add the ammonium bicarbonate aqueous solution into a separatory funnel and slowly drip it into the prepared modified rare earth nitrate-gluconic acid aqueous solution. During the dripping process, a large amount of white precipitate will be observed in the mixed solution; let the mixed solution stand in the beaker for 30 min, discard the clear supernatant, and then transfer the white precipitate at the bottom into a Buchner funnel lined with filter paper and filter it with a suction filter. After filtering, the white solid is deducted into an evaporating dish and placed in an oven at 80°C for 12 h for drying. The dried white solid is transferred into a crucible and placed in a muffle furnace for calcination at 750°C for 3 h, the calcined solid is ground into fine powder using a grinder, and then prepared into an aqueous solution with a solid content of 25% using deionized water, and placed in a sand mill for wet sand grinding at 3000 r / min for 2 h. The sand-milled slurry is placed in a vacuum drying oven for full drying, and the dried solid is finally ground into fine powder using a grinder again to obtain a rare earth composite material with a layered structure;
[0050] (2) Take 10 L of natural rubber latex, add 500 mL of curing agent 8530, 500 mL of dispersant 2120, and 100 g of rare earth composite material, mix the above materials and add them to a mixer, heat the mixer to 120°C, and use high-speed stirring to form a rubber liquid with a uniform mixture of raw materials; fully immerse the mold in the rubber liquid and rotate it horizontally for 10 min to ensure that the rubber liquid covers the glove mold, and then transfer the mold to an oven for drying at 80°C for 12 h; after drying, transfer the mold to a vulcanization chamber for vulcanization treatment, and then use infrared treatment to completely evaporate the moisture inside the product, and then use deionized water to clean the dust and impurities on the surface, and then transfer it to an oven for drying again. After the above series of treatments, the product has better toughness and strength and can be directly demolded manually.
[0051] Figure 1 are the puncture resistance performance indicators of the rubber products finally prepared in Example 1 and Comparative Examples 1-3. The rubber product obtained in Example 1 has the best puncture resistance performance, with a puncture force / thickness (N / mm) of 35.00. The rubber products obtained in Comparative Examples 1-3 have the following indicators: 28.83, 26.38, and 25.37, respectively, which are all lower than those in Example 1. Figure 2-3 The colony diagrams of the rubber products finally prepared in Example 1 and Comparative Examples 1-3 are the test colonies against Escherichia coli and Staphylococcus aureus.
[0052] Figure 2This is a colony diagram of the anti-E. coli test, from left to right are Example 1 and Comparative Examples 1-3. The number of colonies in Example 1 is the least, so its anti-E. coli rate is the highest. The anti-E. coli rates in the comparative examples are Comparative Example 2, Comparative Example 3, and Comparative Example 1 from high to low.
[0053] Figure 3 It is a colony diagram of the anti-Staphylococcus aureus test, from left to right are Example 1 and Comparative Examples 1-3. The number of colonies in Example 1 is the least, so its anti-Staphylococcus aureus rate is the highest. The anti-Staphylococcus aureus rates in the comparative examples are Comparative Example 2, Comparative Example 3, and Comparative Example 1 from high to low.
[0054] In the modification method of Comparative Example 1, heating is not performed, so the molecular collision frequency and strength are insufficient when the lignocellulosic substances in the mushroom chaff powder react with the rare earth ions, resulting in the inability to fully adsorb the rare earth ions, thereby failing to provide a large number of stable adsorption sites for them. Therefore, the rare earth ions contained in the finally formed rubber product are lower than the rare earth elements contained in the rubber product in Example 1, resulting in poor anti-puncture and antibacterial properties; in Comparative Example 2, the amount of mushroom chaff powder added is small, and it is also unable to fully react with the rare earth ions, and more rare earth ions with stable adsorption sites wrapped with lignocellulosic substances cannot be formed, resulting in reduced anti-puncture and antibacterial properties. In Comparative Example 3, mushroom chaff powder is not used for modification. Compared with the modification method of Example 1, the rubber product obtained does not have a chelate complex formed by chelation of functional groups such as carboxyl, hydroxyl, carbonyl, and O-glycosidic bonds with rare earth ions, and simply relies on the efficacy of rare earth ions to perform its functions, so its anti-puncture and antibacterial effects are poor.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial rare earth stab-proof rubber product, characterized in that: The rubber product comprises the following raw materials in parts by weight: 80-120 parts of rubber latex, 3-7 parts of curing agent, 3-7 parts of dispersant, 1-2 parts of rare earth composite material; The preparation method of the rare earth composite material comprises the following steps: Step 1 is to add modified rare earth nitrate and gluconic acid into deionized water, and obtain a modified rare earth nitrate-gluconic acid aqueous solution after complete dissolution; Step 2 is to add ammonium bicarbonate into deionized water and obtain an ammonium bicarbonate aqueous solution after the ammonium bicarbonate is completely dissolved; Step 3 is to slowly drop the aqueous solution of ammonium bicarbonate into the aqueous solution of modified rare earth nitrate-gluconic acid, and then filter, wash, dry, calcine, grind, sand mill, and vacuum dry to obtain the rare earth composite material; The solid-liquid ratio of the modified rare earth nitrate, gluconic acid and deionized water in step 1 is 2-11 g: 1-2 g: 35-45 mL; the solid-liquid ratio of ammonium bicarbonate and deionized water in step 2 is 2-5 g: 15-25 mL; The volume ratio of the aqueous solution of ammonium bicarbonate to the aqueous solution of modified rare earth nitrate-gluconic acid in step 3 is 8-10:18-22; The preparation method of the modified rare earth nitrate in step 1 comprises the following steps: Adding the mushroom dregs powder to a sodium hydroxide solution, stirring evenly, then adding a rare earth nitrate solution thereto, mixing evenly, subjecting the obtained mixed solution to magnetic stirring under heating conditions, and drying, grinding, and sieving after the reaction is completed to obtain the modified rare earth nitrate; The mass concentration of the sodium hydroxide solution is 3-5%; the concentration of the rare earth nitrate solution is 0.2-1.0 mol / L; The solid-to-liquid ratio of the mushroom residue powder to the sodium hydroxide solution and the rare earth nitrate solution is 1-2g: 15-25mL: 15-25mL; The temperature of the heating step in the preparation method of the modified rare earth nitrate is 70-80°C; The rare earth nitrate in the rare earth nitrate solution is at least one of cerium nitrate hexahydrate, lanthanum nitrate hexahydrate or yttrium nitrate hexahydrate.
2. The antibacterial rare earth stab-proof rubber product according to claim 1, characterized in that: The temperature of the drying step in step 3 is 70-90°C and the time is 10-15 hours; the temperature of the calcining step in step 3 is 700-750°C and the time is 2-4 hours; the sanding step in step 3 is wet sanding at a rate of 2500-3000 r / min and the time is 2-4 hours.
3. The antibacterial rare earth stab-proof rubber product according to claim 1, characterized in that: The speed of the magnetic stirring step in the preparation method of the modified rare earth nitrate is 600r / min, and the time is 0.5-1.0 hour; the temperature of the drying step in the preparation method of the modified rare earth nitrate is 70-90°C, and the time is 16-32 hours; the mesh number of the sieve in the screening step in the preparation method of the modified rare earth nitrate is 200-300 mesh.
4. The method for preparing the antibacterial rare earth stab-resistant rubber product according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing rubber latex, curing agent, dispersant and rare earth composite material, demoulding, drying, vulcanizing and washing to obtain the antibacterial rare earth stab-proof rubber product.
Citation Information
Patent Citations
Novel antibacterial polyester as well as preparation method and application thereof
CN118702904A
Rare earth modified antibacterial functional master batch for fibers and preparation method thereof
CN118703031A